2008
DOI: 10.1007/s10333-008-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of earthworms and ants on soil properties of paddy fields in North-East Thailand

Abstract: As soil engineers, earthworms and ants play major roles in soil functioning, especially in modifying soil physical and chemical properties. This study was conducted in a very constraining environment, i.e., paddy fields which have anoxic conditions (approximately four months per year), and which are affected by soil salinisation during the dry period (approximately eight months per year). This study points out that despite those very adverse conditions, soil invertebrates must be taken into account in the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Jouquet et al . (2008) previously reported the possible effect of ants and earthworms on soil particle size and soil organic matter dynamics in paddy fields in the same study area. In Indonesia, Widyastuti (2002) also demonstrated that soil macrofauna plays an important role in promoting litter decomposition and mineral nitrogen dynamics.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Jouquet et al . (2008) previously reported the possible effect of ants and earthworms on soil particle size and soil organic matter dynamics in paddy fields in the same study area. In Indonesia, Widyastuti (2002) also demonstrated that soil macrofauna plays an important role in promoting litter decomposition and mineral nitrogen dynamics.…”
Section: Discussionmentioning
confidence: 89%
“…Few studies have examined the impact of soil macrofauna in the functioning of partially flooded ecosystems such as paddy fields, although ecosystem functions and services may be influenced by its biodiversity. Jouquet et al (2008) previously reported the possible effect of ants and earthworms on soil particle size and soil organic matter dynamics in paddy fields in the same study area. In Indonesia, Widyastuti (2002) also demonstrated that soil macrofauna plays an important role in promoting litter decomposition and mineral nitrogen dynamics.…”
Section: Biodiversity and Ecosystem Services In Paddy Fieldsmentioning
confidence: 97%
“…This demonstrates that the species is compatible with at least organic farming and that conservation of the species is not difficult, which is increasingly important in the world. Jouquet et al (2008b) showed the casts produced by Glyphidrilus sp. can be considered as patches of nutrients in paddy fields.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that there is no selectivity in relation to the mineral particles size ingested by the worms, at least within this study area. A greater proportion of fine fraction materials have been reported in casts relative to undisturbed soil; however, the intensity of this granulometric selection likely depends both on the pre-existing soil texture as well as on the ecological behavior of earthworms (BLANCHART et al, 2004, RUIZ et al, 2006JOUQUET et al, 2008). However, only large earthworm casts and their sand, silt, and clay fractions were analyzed here.…”
Section: Physical and Chemical Attributesmentioning
confidence: 96%